Peran Pegadaian Syariah Terhadap Kesejahteraan Masyarakat - Rizky, Syafnur M; Winario, Mohd (EL-EMIR Institute, 2024)
This research aims to analyze the role of Sharia Pawnshops on community welfare. The research results show that Sharia Pawnshops have an important role in improving community welfare, especially for the lower middle economic group. Through financing schemes that comply with sharia principles, Pegadaian Syariah can help people obtain additional capital to develop their businesses. Apart from that, Sharia Pegadaian also plays a role in providing financial education to the public so that they can manage their finances well and avoid financial shocks. However, there is still an imbalance in public understanding regarding the benefits and risks of using Pegadaian Syariah's service products, so efforts are needed from Pegadaian Syariah to increase financial literacy among the public. Overall, the results of this research show that Sharia Pawnshops have a significant role in improving community welfare.